Gut fungal profile in new onset treatment-naïve ulcerative colitis in Saudi children - Mohammad El Mouzan; Abdulaziz Al Quorain; Asaad Assiri; Abdullah Almasoud; Badr Alsaleem; Ahmed Aladsani; Ahmed Al Sarkhy (The Saudi Journal of Gastroenterology)
Background: Although the role of fungi in gut inflammation in IBD has been suggested, data are still limited in ulcerative colitis (UC). Our aim was to describe the gut fungal profile in a pediatric UC in Saudi Arabia. Methods: Fecal samples from children with UC and control samples provided by healthy school children were collected. The fungal DNA was analyzed using Shotgun metagenomic procedures. Shannon alpha diversity, beta diversity, differential abundance, random forest classification algorithm, and area under the curve were analyzed. Results: There were 20 children with UC and 20 healthy school children. The median age and range were 13 (0.5–21) and 13 (7–16) years for children with UC and controls, respectively. Male subjects were 40% and 35% for UC and controls, respectively. At diagnosis, the UC extent was E4 (38%); E3 (25%); E2 (37%) and 35% had a PUCAI ≥65. The reduction of alpha diversity and the significant dissimilarity in children with UC were similar to those of most published studies. However, a significant difference was found at all taxa levels with a remarkable enhancement of Candida genus and Saccharomyces cerevisiae in children with UC. Three species were identified as fungal signatures and an area under the curve of 98.4% (95.1–100% CI), indicating an association with UC that has not been reported thus far. Conclusion: We report significant fungal dysbiosis in children with UC consistent with published literature. However, the report of potential fungal signature and a strong association with UC deserves further studies with a bigger sample size from other populations.